2014
DOI: 10.1111/resp.12379
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric validation of a cystic fibrosis knowledge scale

Abstract: This study is an important first step in a line of research that aims to develop and empirically validate a psycho-educational adherence intervention for improving quality of life and treatment outcomes among adult CF patients. The CF knowledge scale has potential applications as a clinical teaching tool with patients and health-care providers and could be used as an outcome measure in CF educational intervention studies aimed at optimizing CF treatment knowledge, adherence and quality of life among CF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
(34 reference statements)
1
21
0
1
Order By: Relevance
“…One study has found that adherence to medication is related to children’s and parents’ knowledge on treatment details 13. Another recent study demonstrated a potential association between CF knowledge using a validated CF knowledge scale and patient-reported treatment adherence in a post hoc analysis 14. To our knowledge, the impact of patient knowledge of lung function (ie, FEV 1 % predicted) and the intended benefits of prescribed medications on medication adherence has not been examined previously in CF.…”
Section: Introductionmentioning
confidence: 99%
“…One study has found that adherence to medication is related to children’s and parents’ knowledge on treatment details 13. Another recent study demonstrated a potential association between CF knowledge using a validated CF knowledge scale and patient-reported treatment adherence in a post hoc analysis 14. To our knowledge, the impact of patient knowledge of lung function (ie, FEV 1 % predicted) and the intended benefits of prescribed medications on medication adherence has not been examined previously in CF.…”
Section: Introductionmentioning
confidence: 99%
“…Diyabet, hipertansiyon ve kistik fibrozis hastalarında yapılan çalışmalar bireylerin hastalık hakkındaki bilgi eksikliğinin sağlıkla ilgili davranışlarda olumsuzluğa, yönlendirme yapılsa bile teşhisin konabilmesi için gerekli yerlere baş-vurmamalarına ve tedavide koopere olmamalarına yol açtığını göstermektedir. [16][17][18] Owens 19 yaptığı çalışmada doktorların, çocuklarda bir uyku problemi varsa bunun ebeveynler tarafından belirlenip kendilerine belirtilmesini beklediklerini göstermiştir. Pediatrik uyku apnesinin çocukların gelişiminde ve sağlığında yaratabileceği olumsuzluklar düşünüldüğünde ebeveynlerin bilgi düzeylerinin belirlenmesi bu nedenle büyük önem taşı-maktadır.…”
Section: Discussionunclassified
“…6,13,14,20 Studies of patients with CF, particularly children, have consistently shown adherence rates of less than 50%. It is an acknowledged, serious, and persistent problem.…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence to these therapies can lead to increased hospital admissions, decreased pulmonary functioning, and shorter life spans. 6,13,14 In this era of new treatments and improved lifespans for patients with CF, 9,15 the importance of adherence cannot be underestimated.…”
Section: Introductionmentioning
confidence: 99%